MENINGKATKAN KEMAMPUAN PASSING BAWAH BOLA VOLI MENGGUNAKAN PERMAINAN 3 ON 3 DENGAN METODE DISCOVERY LEARNING PADA SISWA KELAS VII SMP N 5 RAMBAH HILIR TP.2020/2021 - Yaya Sunarya Saragih (JURNAL PENDIDIKAN ROKANIA, 2022)
This study aims to improve volleyball bottom passing skills in physical education learning using 3 on 3 games for seventh grade students of SMP Negeri 5 Rambah Hilir. This research is a classroom action research that takes place in 2 cycles. The data collection methods used were observation, and performance tests. The results showed that the learning process has increased from each cycle, students also look more enthusiastic and feel happy in participating in learning so they are not bored. The results of students' passing skills also increased. In cycle 1, students who achieve the minimum completeness criteria (KKM) are 21 students or 53.85%, increasing in cycle 2 to 30 students who reach the minimum completeness criteria (KKM) or 76.92%. The average value of the class also increased which previously in cycle 1 was 70 and then increased to 81. From these results it can be concluded that using 3 on 3 games can improve the learning process and volleyball passing skills of seventh grade students of SMP Negeri 5 Rambah Hilir.